Heavy Metal Contamination on Shallot Fields In Bantul Regency, Yogyakarta - Cicik Oktasari Handayani; Edi Martono; Rika Harini (UNIVERSITY OF LAMPUNG, 2022)
Shallot cultivation usually uses very intensive agrochemicals that could affect the soil’s chemical properties and contaminate agricultural land by increasing the content of heavy metals. The use of agrochemicals is closely related to the behavior of farmers. The research aimed to study the heavy metal contamination and soil chemical properties in shallot fields and analyze the relationship between farmer behavior in using fertilizers and pesticides with a heavy metal concentration in agricultural land. The research was conducted in Srigading Village, Batul, Yogyakarta. Soil samples as many as 30 samples were taken from the shallot fields before harvest using a purposive sampling method and were analyzed for heavy metal concentrations of Pb, Cd, Ni, Co, Cr, and other soil chemical properties. Interviews were also conducted with landowners or farmers at the soil sampling location. Analysis of interview data was carried out by scoring each qualitative data into quantitative data through a questionnaire and testing the correlation between farmer behavior and heavy metal content. The results found that the shallot fields in the Srigading Village, Bantul contain heavy metals Pb, Cd, Cr, Co, and Ni with concentrations below soil quality standard. The soil organic carbon content in shallot fields has a low value. Farmer behavior has a weak negative correlation with heavy metal content in the soil.